The Unique Range Set of Meromorphic Functions in an Angular Domain - Hong-Yan Xu; Zu-Xing Xuan; Hua Wang (The Scientific World Journal)
By using Tsuji's characteristic, we investigate uniqueness of meromorphic functions in an angular domain dealing with the shared set, which is different from the set of the paper (Lin et al., 2006) and obtain a series of results about the unique range set of meromorphic functions in angular domain.